2016
DOI: 10.17576/mjas-2016-2005-25
|View full text |Cite
|
Sign up to set email alerts
|

HYTOCHEMICAL SCREENING, TOTAL FLAVONOID AND PHENOLIC CONTENT ASSAYS OF VARIOUS SOLVENT EXTRACTS OF TEPAL OF Musa paradisiaca

Abstract: The objective of this research is to conduct the preliminary phytochemical screening, total flavonoid and phenolic contents assays of various solvent extracts of tepal of Musa paradisiaca. Phytochemical screening was carried out according to the method of Trease and Evans, total flavonoid content was measured by the aluminium chloride colorimetric assay and total phenolic content was estimated spectrophotometrically by Folin-Ciocalteau method. -Preliminary phytochemical screening reveals the presence of phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 26 publications
1
47
0
1
Order By: Relevance
“…these biologically active compounds are generally soluble in H 2 O, hydroalcoholic and polar acetone solvent and gives sediments binding by proteins [19]. Several scientific pieces of evidence showed that phenolics were traditionally used for prevention of inflammation of the mouth and to treat wounds, hemorrhoids, and diarrhea [11,[20][21][22]. Plants, animals, and microorganisms are considered as the sources of natural product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…these biologically active compounds are generally soluble in H 2 O, hydroalcoholic and polar acetone solvent and gives sediments binding by proteins [19]. Several scientific pieces of evidence showed that phenolics were traditionally used for prevention of inflammation of the mouth and to treat wounds, hemorrhoids, and diarrhea [11,[20][21][22]. Plants, animals, and microorganisms are considered as the sources of natural product.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in Pilipino ripe banana samples, the maximum potential was in n-hexane and minimum in water followed by order of n-hexane > n-butanol > methanol > ethyl acetate > chloroform > water ( Table 5). From the literature, it has been obtained that the bananas crude extracts contain some primary active compound, e.g., tannin, glycosides, phenolic compounds, triterpenes, flavonoids, lanosterol, and a-amyrin [3,[8][9][10][11]22]. These biologically active compounds can able to neutralize the level of DPPH with color change by their hydrogen donating ability [15].…”
Section: Discussionmentioning
confidence: 99%
“…The methanol extract was iltered and 2 ml of sulfuric acid was added and was shaken to get 2 layers. The top layer (sulfate) was taken 5 drops, then 1 drop of Dragendorf reagent was added and the formation of orange deposits showed the presence of alkaloids (Rao and Mohd, 2016).…”
Section: Alkaloid Testmentioning
confidence: 99%
“…After being shaken for 30 seconds, changes occurred. If the permanent solid foam was formed (permanently for 30 seconds), this indicated the presence of saponins (Rao and Mohd, 2016).…”
Section: Saponin Testmentioning
confidence: 99%
See 1 more Smart Citation